Modern sufism and classical sufism - Yulianti, Silviyatus (Maliki Interdisciplinary Journal, 2024)
Sufism, also known as Tasawuf, is a religious tradition that has been discussed since the late 2nd century of the Hijri calendar. The term "Tasawuf" is believed to be associated with a rough type of clothing called "shuff" or coarse wool. Sufism has a profound focus on spiritual peace and happiness, without carrying any negative connotations of being an obsession. Beyond mere clothing, Tasawuf serves as a controller of various forces that could disrupt the balance of the soul, helping individuals become resilient to negative influences from the external environment, thereby bringing inner peace and happiness. This article aims to explore the distinctions between classical Sufism and modern Sufism, using a literature review approach and gathering data from interviews and document studies. Through this study, it is hoped to provide a deeper understanding of the evolution of Sufism from the past to the present.